Clinical impact of antibodies to Sp100 on a bacterial infection in patients with primary biliary cholangitis. Issue 11 (8th October 2021) - Himoto, Takashi; Yamamoto, Shuhei; Morimoto, Kaho; Tada, Satoshi; Mimura, Shima; Fujita, Koji; Tani, Joji; Morishita, Asahiro; Masaki, Tsutomu
Abstract: Background: A specific antinuclear antibody for primary biliary cholangitis (PBC) is anti‐Sp100, which was recognized as a serological marker of concurrent urinary tract infection. We sought to determine the clinical characteristics of PBC patients who had anti‐Sp100. Patients and Methods: Fifty‐one patients with PBC and 10 healthy controls (HCs) were enrolled. Anti‐Sp100 were determined with an ELISA method. Lipopolysaccharide‐binding protein (LBP) was measured as a serological hallmark for bacterial infection. The correlations of anti‐Sp100 with demographic, laboratory, and pathological parameters were investigated. Results: Six of the 51 (11.8%) PBC patients had anti‐Sp100, whereas none of the HCs did. There was no significant difference in the frequency of antimitochondrial antibodies (AMAs) between PBC patients with and without anti‐Sp100 (67% vs. 82%, p  = 0.5839). Biochemical and immunological parameters were not associated with the emergence of anti‐Sp100 in these patients. The clinical stage by Scheuer classification was not correlated with the existence of anti‐Sp100. No significant difference in the serum LBP levels was found between PBC patients with and without anti‐Sp‐100, although serum LBP levels were significantly higher in PBC patients with anti‐Sp100 than in HCs (8.30 ± 2.24 ng/ml, vs. 5.12 ± 2.48 ng/ml, p  = 0.0022). The frequency of granuloma formation was higher in the liver specimens of PBC patients with anti‐Sp100 than in those without anti‐Sp100 (67% vs 29%, p  = 0.0710). Conclusion: anti‐Sp100 does not become a complementary serological marker for PBC in AMA‐negative patients. A bacterial infection may trigger the production of anti‐Sp100. Another factor is required to initiate the autoantibody production. Abstract : Six of the 51 (11.8%) primary biliary cholangitis patients had anti‐Sp100. No significant difference in the serum LBP levels was found between PBC patients with and without anti‐Sp100, although serum LBP levels were significantly higher in PBC patients with anti‐Sp100 than in HCs (8.30 ± 2.24 ng/ml, vs. 5.12 ± 2.48 ng/ml, p  = 0.0022). The frequency of granuloma formation was higher in the liver specimens of PBC patients with anti‐Sp100 than in those without anti‐Sp100 (67% vs 29%, p  = 0.0710). However, no significant difference in serum LBP level was found between PBC patients with and without granuloma formation (7.37 ± 1.90 vs. 7.21 ± 1.90 ng/ml, p  = 0.8399).